If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 = 1 + -3z Solving 6 = 1 + -3z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '3z' to each side of the equation. 6 + 3z = 1 + -3z + 3z Combine like terms: -3z + 3z = 0 6 + 3z = 1 + 0 6 + 3z = 1 Add '-6' to each side of the equation. 6 + -6 + 3z = 1 + -6 Combine like terms: 6 + -6 = 0 0 + 3z = 1 + -6 3z = 1 + -6 Combine like terms: 1 + -6 = -5 3z = -5 Divide each side by '3'. z = -1.666666667 Simplifying z = -1.666666667
| 4x+x^2-25=2304 | | 19x-3=21X-5 | | 5x+19x-7=6(4x+3) | | 14x-118=62+5x | | h=-16t^2-11t+120 | | 2x-187=72-5x | | 2x-(x-1)=5(x-3) | | 42x^2-5x-3=0 | | -20=2(w+7)-4w | | t/25=14/10 | | -9x-73=67-14x | | 4x+26x-9=6(5x+5) | | 3x-6=40 | | 3x-6+2x-4=30 | | 5x-40=8x+11 | | 28-4x=13-9x | | -161+8x=2x+99 | | 12x+15=5x+7 | | (x-1)+(x-1)=g | | y-2=(22-y)^(1/2) | | -114-2x=210+7x | | (x^2)-2x-2.5=0 | | 3a-27=54+9a | | 3x-22=13+4x | | -14+10x=11x+13 | | 5(x-2)=80-5x | | 5x-3=67-9x | | g(x)=-log^2(x-3)+1 | | -91+3x=-x+37 | | g(x)=-log^2(x-3) | | 8x+1=7-20 | | 2/3(15)=10 |